Comparative Osmoregulation Response of Common Carp (Cyprinus carpio) and Gourami (Osphronemus gouramy) Under Seawater Exposure - I Wayan Merta; Kusmiyati Kusmiyati (Jurnal Pijar MIPA, 2026)
Homeostasis is an essential physiological process that functions to maintain the stability of an organism's internal conditions, primarily through osmoregulation mechanisms in aquatic animals. This study aims to: 1. Compare the physiological responses of osmoregulation between goldfish (Cyprinus carpio) and gourami fish (Osphronemus gouramy) after being given treatment in the form of exposure to seawater. 2. Increasing students' insight into animal physiology, especially osmoregulation material in fish. The method used was an experiment with two treatment groups, each group replicated 15 times. Data collection was conducted through direct observation of the fish's survival time and respiratory frequency. Data analysis was carried out using a t-test at the 5% significance level. The results showed that gourami had a higher average survival time (41.80 minutes) than goldfish (16.33 minutes). In contrast, goldfish showed a higher respiratory rate, indicating greater osmotic stress. Based on the t-test, a significant value of 0.00 <0.05 was obtained. This study concludes that there is a significant difference in survival between goldfish and gourami. Gourami fish have better osmoregulatory adaptation abilities than goldfish in high-salinity environments. The findings provide valuable insights into species-specific osmoregulatory adaptations to salinity stress and can serve as an effective learning resource for enhancing students' understanding of animal physiology and aquatic environmental adaptation.